The Effect of mHealth on Preventing Anemia in Adolescent Girls: A Literature Review - Rahayu, Sri; Said, Saifulaman Muhamed; Sansuwito, Tukimin Bin (International Journal of Health Sciences, 2024)
A significant number of teenage girls are at risk of developing anemia. When it comes to adolescent girls, there are still significant knowledge, attitudes, and practice gaps, as well as health education gaps, which can affect anemia. App-based health technology, such as mobile health (mHealth), is a promising tool that has the potential to overcome obstacles and give suitable health guidelines as part of efforts to promote, prevent, cure, and rehabilitate patient health. Objective: to assess the impact of MHealth interventions on the prevention of anemia in adolescent girls. Method: This research is a review of the existing literature. With the assistance of the publish or perish application, data sources were gathered in the form of publications published in national and international journals between the years 2019 and 2023. These articles were obtained from the PubMed database and Google Scholar. PICOS was used as the inclusion and exclusion criteria for the selection of articles, and the selection process was accordingly. This research was carried out in a manner that was compliant with the PRISMA recommendations. A total of 352 articles were collected from the search results. Next, an elimination process was performed based on predefined criteria based on PICOS requirements, resulting in a total of nine studies included in the review (n = 9). This was depicted in PRISMA. The study utilized various mHealth apps, including WANTER, TEENFIT, LADIES, She Smart, eHealth, Android-based apps, E-WoHealth, Aneminfo, and Android apps that use videos. The findings suggest that comprehensive implementation of health apps can effectively reduce the occurrence of anemia in adolescent girls. Conclusion: The utilization of mHealth applications in health technology has the potential to enhance knowledge, modify behavior and attitudes more effectively, and facilitate the implementation of anemia prevention measures to decrease and avert anemia.